2002
DOI: 10.1046/j.1469-7580.2002.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of immune cells in animal models for inherited neuropathies: facts and visions*

Abstract: Mice heterozygously deficient in the peripheral myelin adhesion molecule P0 (P0+/-mice) are models for some forms of Charcot-Marie-Tooth (CMT) neuropathies. In addition to the characteristic hallmarks of demyelination, elevated numbers of CD8-positive T-lymphocytes and F4/80-positive macrophages are striking features in the nerves of these mice. These immune cells increase in number with age and progress of demyelination, suggesting that they might be functionally related to myelin damage. In order to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 52 publications
(107 reference statements)
2
12
0
2
Order By: Relevance
“…In mice deficient in Cx32, a model for CMT1X, T-lymphocytes and macrophages were induced, and macrophages showed close apposition to degenerating myelin, suggesting that involvement of T-lymphocytes and macrophages is a common pathogenetic feature in various forms of slowly progressive inherited neuropathies [19,20]. Another study revealed that Cx32-deficient mice crossbred with mice deficient in mature T-and B-lymphocytes (RAG-1-deficient mice) showed less severe myelin degeneration in the absence of lymphocytes [21].…”
Section: Discussionmentioning
confidence: 99%
“…In mice deficient in Cx32, a model for CMT1X, T-lymphocytes and macrophages were induced, and macrophages showed close apposition to degenerating myelin, suggesting that involvement of T-lymphocytes and macrophages is a common pathogenetic feature in various forms of slowly progressive inherited neuropathies [19,20]. Another study revealed that Cx32-deficient mice crossbred with mice deficient in mature T-and B-lymphocytes (RAG-1-deficient mice) showed less severe myelin degeneration in the absence of lymphocytes [21].…”
Section: Discussionmentioning
confidence: 99%
“…Because we did not detect widespread Nav1.8 expression in developing nerves (data not shown), it is unlikely that its increased expression in Trembler-J nerves represents a persistence/recapitulation of development, as has been argued for Nav1.2 in the CNS (see above). The nodal expression of Nav1.8 could be related to inflammatory changes that occur in demyelinating neuropathies (Maurer et al, 2002), as Nav1.8 expression increases after nerve injury (Akopian et al, 1999;Gold et al, 2003;Roza et al, 2003). This possibility seems unlikely because there were no obvious differences in the number of Nav1.8-positive neurons in the lumbar ganglia or in the intensity of immunostaining of unmyelinated axons between Trembler-J and WT mice (data not shown) (cf.…”
Section: Channel Subunits In Trembler-j Nodesmentioning
confidence: 91%
“…However, the signals that mediate this cell-to-cell communication are largely unknown. Loss of trophic support by damaged Schwann cells may contribute, and recent data suggest that inflammation is involved [206]. Further work will focus on the identification of other genes that can cause CMT.…”
Section: Closing Remarksmentioning
confidence: 97%